ANALISIS FAKTOR YANG BERHUBUNGAN PENURUNAN KUNJUNGAN BALITA KE POSYANDU DI PUSKESMAS RAMBUNG MERAH TAHUN 2020 - zulfianidar, zulfianidar (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2021)
Posyandu is the spearhead of basic public health services. The purpose of developing this Posyandu is to aim at health development, which is to accelerate the reduction of infant and under-five mortality rates from birth, to accelerate the acceptance of the norm of happy and prosperous small families and the development of community activities in accordance with their needs and abilities. The purpose of this study was to analyze the factors influencing the decrease in visits of under-fives to posyandu at Puskesmas Rambung Merah in Simalungun Regency. The method in this study uses quantitative methods. The technique used for data collection was the Accidental Sampling technique with a total of 91 respondents, namely mothers with children under five. The type of data used is primary data and secondary data. Data obtained using a questionnaire and then analyzed the data using logistic regression test. Based on the results of the study revealed that there are 5 factors that cause the low number of toddlers visiting the posyandu at Puskesmas Rambung Merah, namely: 1). Occupational Factor, 2). Knowledge Factors, 3). Attitude Factor. 4) Environmental Factors and 5) Schedule Factors. Based on the logistic regression analysis, the influence of low visits was the most dominant is the attitude of the mother, p value = 0.002 and OR = 4.647. It can be concluded that the mother's attitude that is not good is a risk factor for a decrease in toddler visits with a risk of 4,678 x compared to a good mother's attitude.